A LITERATURE REVIEW OF PHYSICAL, PSYCHOLOGICAL, AND SOCIAL ASPECTS IN FILARIAL LYMPHEDEMA PATIENTS - Kattari, Raisah Putri; Nihar, Mahdiyyah Husna; Eka Ningsih, Fitriani Putri; Dwi Mulyani, Rizka Rosa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Filariasis disease is caused by filarial worms and transmitted by mosquitoes. Filariasis lymphedema is considered scary because it can cause permanent body defects that are aesthetically detrimental and reduce patient mobility. In addition, this disability also causes psychological and social problems for patients. The objective is to conduct a literature review of filarial lymphedema patients' physical, psychological, and social aspects. Methods: A literature review was conducted from the digital database of Pubmed, BMC, PLOS neglected tropical diseases, SAGE journal, and Google Scholar published in English between 2000 until march 2023. The author used the terms “physical” AND “psychological” OR “psychosocial” AND “social” AND “filarial lymphedema”. And the last step was all articles were reviewed, articles under review were original research design, cross-sectional studies, cohort studies, descriptive studies, quantitative, and qualitative studies. Results: The nine papers that made up the literature review were released in the years 2005 through 2023. The majority of research demonstrated that physical disabilities resulting from lymphatic filariasis induce reduced physical function in patients. Additionally, seven studies discovered that individuals with lymphatic filariasis experienced depression as a result of their physical limitations, social isolation brought on by stigma, sleep issues, anxiety, marital issues, and financial difficulties.. This literature review found that filarial lymphedema can affect the physical and social aspects of the patients and gradually can affect the mental health of patients. morbidity management program of filarial lymphedema needs to be improv and promote so it can reduce stigma, psychology, the social and physical burden due to lymphedema filariasis